Interactive Effect of Fertilization and Biochar on the Growth of Juniperus scopulorum under Various Shading and Irrigation Conditions - Rahman, Sk Abidur; Lee, Hyun Ju; Carayugan, Mark Bryan; Wijaya, Bangun Adi; Youn, Woo Bin; Yeo, Jong Chan; Park, Sang Hyun; Kong, Ye Jin; Kim, Hyung Won; Carvalho, Julia Inacio; Latt, Myo Min; Hintural, Wencelito Palis; An, Ji Young; Park, Byung Bae (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
The global demand for landscape trees has been amplified with the increasing anthropogenic activity. South Korea has also witnessed a surge in demand for landscape plants, among others, Juniperus scopulorum gaining popularity for its ecological, economic, adaptability, and management attributes. However, the optimum management practice for high-quality Juniperus seedling production in South Korea remains unknown. This research was conducted on the one-to-two-years-old two cultivars of J. scopulorum, namely Blue Angel and Blue Heaven seedlings, to investigate the combined impacts of varying fertilizer concentrations (0 ppm, 150 ppm, 300 ppm) and biochar content (0% and 20%) under contrasting shading intensities (0%, 35%, 55%) and irrigation levels (200 ml, 400 ml, 800 ml). The study revealed that biochar and fertilizer amendment significantly (p < 0.01 and p < 0.05) enhanced the height and root collar diameter growth in Blue Angel and Blue Heaven in light shade intensity (0–35%) and higher irrigation (400–800 ml) conditions. Similarly, seedlings planted in 20% biochar and 300 ppm fertilizer yielded higher foliar, stem, and root biomass in low shade and higher irrigation conditions. The amount of shade and irrigation and their interactions significantly affected the morphological growth of seedlings for both cultivars, causing positive interaction with soil amendment (biochar and fertilizer application). These findings suggest that efficient seedling production of J. scopulorum management should focus primarily on light shading and moderate irrigation under biochar and higher fertilizer application. The research contributes valuable insights toward optimizing management practices and reducing costs associated with J. scopulorum seedling production in the region. Keywords: biochar, fertilizer, irrigation, Juniperus scopulorum, shading